The association between cannabis vaping and other substance use - Ruoyan Sun; David Mendez; Kenneth E. Warner (Addictive Behaviors Reports, 2023)
Introduction: The popularity of cannabis vaping has increased rapidly, especially among adolescents and young adults. We posit some possible explanations and, to evaluate them, examine whether cannabis vapers differ from non-vaping cannabis users in other substance use. Methods: Using nationally representative data from the Population Assessment of Tobacco and Health (PATH) Study wave 5 (Dec. 2018-Nov. 2019), we assessed the association between cannabis vaping and other substance use. A total of 1,689 adolescents and 10,620 adults who reported cannabis use in the past 12 months were included in the study. We employed multivariable logistic regressions to assess the association between cannabis vaping and other substance use. Results: Among past 12-month cannabis users, compared with those who do not vape cannabis, participants who vape cannabis had higher risks of using alcohol (adjusted relative risk [aRR] = 1.04, 95 % CI, 1.01–1.07), cigarettes (aRR = 1.09, 95 % CI, 1.02–1.15), cigars (aRR = 1.17, 95 % CI, 1.06–1.30), other tobacco products (aRR = 1.29, 95 % CI, 1.14–1.45), electronic nicotine products (aRR = 4.64, 95 % CI, 4.32–4.99), other illicit drugs (aRR = 1.53, 95 % CI, 1.29–1.80), and misuse of prescription drugs (aRR = 1.43, 95 % CI, 1.19–1.72). Compared to older cannabis vapers, younger cannabis vapers were at risk of using more other substances. Cannabis vaping was associated with all seven measures of substance use among young adults. Conclusions: Compared to non-vaping cannabis users, cannabis vapers have higher likelihood of using other substances. Research is needed to understand why, as well as the implications of the association.